Gaya Kepemimpinan Kepala Sekolah dalam Peningkatan Kinerja Guru - Desi Puspitasari; Ainur Rofiq; Hasyim Asy’ari; Juli Amalia Nasucha (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
The role of the principal as a leader must be distinct from the existing leadership style. The leadership style of a top school influences teachers' good and bad performance in the school institution where they teach. The purpose of this article is to find out: (1) The leadership style of the principal of SDN 1 Munung. (2) Teacher Performance at SDN 1 Munung. This research uses a qualitative approach with the case study method, with a single case study type. Researchers used data collection techniques using observation, interviews, and documentation. Data analysis techniques use data reduction, data presentation, and concluding the data that has been presented and reduced in guaranteeing the validity of the data using triangulation techniques and sources. The results of the study concluded that the leadership of the principal of SD Negeri Munung uses two leadership styles, namely the authoritarian leadership style, in disciplining teachers in daily attendance and completing administration. In comparison, in the following leadership style, namely the democratic leadership style, the principal gives freedom for teachers to develop their abilities in various activities. Subsequent data found that the teacher's performance at SD Negeri Munung was beyond doubt because administrative completion was always early, complete and correct, so SD Negeri Munung was the only Impact school in Jatikalen that received the BOS Performance award.